A Study on Communication Strategies for Response to Korea-EU Technology Regulations: Focusing on the Cases of Response to Energy Efficiency Regulations in the Electronic Display Industry - Jongmin Lee ,; Tae-Yang Kim, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to focus on the EU electronic display energy efficiency-related regulations among the environmental regulations that have become an issue recently. The formal TBT response takes place through government-led channels. However, both the government and private organizations can participate in delivering opinions. The purpose of this study is to study the outcome of the strategy of diversifying into private channels in dialogue between countries that respond to regulations. According to the analysis results, government channels responded mainly to regulations that have a direct impact on exports, and private channels responded to all regulations, including valid evidence. The government's response was from a short-term perspective, while the private channel's response was from a long-term perspective. In response to technology regulation, it has been proven that the government and private channels jointly respond to the need for a dialogue strategy to understand the other party. Therefore, in response to technical regulations, a convergent communication strategy including cultural, social, technological, conventional, and legal perspectives is required. The role of the government and private channels is important in creating an institutional environment in which the results of technological regulation response using convergent communication strategies can promote technological innovation of companies. The Korean government should actively communicate with the EU government through an integrated communication strategy.